Influence of initial season on PVC weathering - Stefano Gardi; Lorenzo Giannone; Gianfranco Sarti; Gianluca Sarti; Michele Costa (Polymer Testing, 2023)
The forecast of the aging behavior of PVC items from the initial stage of formulation design is crucial and relies on accelerated weathering devices. However, running outdoor weathering tests is necessary to achieve more realistic data. Natural aging norms do not specify the initial season of exposure as a parameter, but there are natural outdoor exposure studies outlining the importance of this aspect and indicating that the lowest degradation is obtained when exposure program starts in autumn and the highest one is observed when exposure starts in winter. Therefore, the first aim of this work is to understand if the initial exposure season affects the final results. Another aim, is the investigation of the effect of titanium dioxide loading to understand if the increase in cost formulation, is worth the stabilization effect. The last goal, is the understanding of the effect of stabilizers’ types: tin-based ones mostly used in North America, compared to Calcium Organic ones mostly utilized in Europe. As for the first aim, neither the graphical comparison of discoloration data, nor their statistical analysis confirmed that starting season has a significant effect on degradation. As for the second aim, the same analysis showed that the increase of titanium dioxide from 7 to 9 phr (parts per 100 parts of PVC) is irrelevant on degradation rate. As for the effect of stabilizer type, our analysis indicated that there is a significant difference among only one tin-based stabilizer compared to the others.